2020
DOI: 10.13189/ujer.2020.080742
|View full text |Cite
|
Sign up to set email alerts
|

Program Evaluation on Learning Materials, Tutors, Assessment Matters and Overall Program Structure from ODL Students' Perspective

Abstract: Open Distance Learning (ODL) is an approach in education practices in Open University Malaysia (OUM). One of its programs that are offered through ODL is the Bachelor of Psychology (BPSY) and it is one of the programs with the highest student intake in OUM. Since the program has been commencing for more than 10 years, it is the time to evaluate whether the program needs any revisions or improvements. Thus, the aim of the study is to determine the level of satisfaction of students on the Psychology program offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 3 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…Therefore, they preferred simple assignments over anything else. This particular finding was congruent with a past study by Kamarulzaman and Siew [22], who also concluded that students were least satisfied with the assessment matter.…”
Section: Students' Satisfaction With Open and Distance Learningsupporting
confidence: 90%
See 4 more Smart Citations
“…Therefore, they preferred simple assignments over anything else. This particular finding was congruent with a past study by Kamarulzaman and Siew [22], who also concluded that students were least satisfied with the assessment matter.…”
Section: Students' Satisfaction With Open and Distance Learningsupporting
confidence: 90%
“…Therefore, it was proven that the ODL programme at UTM was professionally structured. Similarly, a previous study by Kamarulzaman and Siew [22] which was conducted at Open University Malaysia (OUM), also found that students were most satisfied with the ODL programme structure.…”
Section: Students' Satisfaction With Open and Distance Learningmentioning
confidence: 56%
See 3 more Smart Citations